Primary prevention of coeliac disease : the utopia of the new millennium? - Catassi, Carlo; Fasano, Alessio; Corazza, Gino Roberto (AIC Italian Coeliac Society, 2003)
A collection of works from a conference that focused on the primary prevention of coeliac disease. Intended for professional public.
Perspectives on coeliac disease ; Volume I
Keywords: Primary Prevention; Celiac Disease; gastroenterologie; preventivní medicína; celiakie; primární prevence; alergologie a imunologie